Do conhece-te a ti mesmo à Parresía: O ensino de Filosofia na Unidade de Ensino Básica Cônego Nestor Cunha em Santa Quitéria do Maranhão - DUTRA, Nívia Maria Rocha (2024)
This qualitative and participatory research aims to analyze the relationships between the teaching of Philosophy in the 9th grade of elementary school and the process of self-knowledge among adolescents. Grounded in Socratic-Platonic philosophy, especially in the concept of Know thyself, and in the critical analysis of Michel Foucault, with an emphasis on the concept of parrhesia, the research investigates how the teaching of Philosophy can promote students' self-knowledge, valuing an education focused on the subject of knowledge. Adolescence, a phase marked by identity formation and existential crises, is often neglected by an educational model that prioritizes the object of knowledge over the development of a deep understanding of oneself. This neglect can result in adolescents becoming distanced from themselves and the world, compromising their sense of belonging and their social relationships. Philosophy, when integrated into the educational context, can offer a transformative response, enabling adolescents to expand their ability to critically interpret both their personal histories and the world around them, fostering a reflective outlook on their own existence. The research is based on the practical experience of the Philosophical Circles held in the municipality of Santa Quitéria do Maranhão, inspired by Paulo Freire's circles of culture and the Socratic method. These circles create a dialogical space where adolescents are encouraged to question their own experiences and to recognize themselves as active subjects in the construction of their stories and identities. At UEB Cônego Nestor Cunha, the teaching of Philosophy is structured around two central approaches: Socratic-Platonic self-knowledge, developed through techniques of the self, and Foucault's critical understanding, which explores how individuals are historically determined. Through these practices, adolescents are invited to engage in self-reflection, question their experiences, and reframe their narratives, fostering a process of personal emancipation and critical development. This investigation, therefore, seeks to contribute to the construction of a Philosophy curriculum that not only values self-knowledge but also promotes the empowerment of young people, enabling them to become active agents in their personal histories and social transformations.